(untitled) (Filološke pripombe, 2019)
This paper discusses an actual problem of the author’s presence in the text on the anagrammatic level. The author is regarded as an onomaturg, but anagramming – special case of an onomaturogy. As an example was chosen the postmodernistic novel "Singapore" and the story "Armageddon" of famous poet-avangardist of XX century Genrih Sapgir.